THE APPLICATION OF CROSS-BORDER INSOLVENCY BANKRUPTCY IN THE EXECUTION OF DEBTOR'S ASSETS IN INDONESIA: A COMPREHENSIVE ANALYSIS - Sairufah, Ani; Yahya, Azhari (Student Journal of International Law, 2023)
Cross-border insolvency is regulated by Law Number 37 of 2004 Concerning Bankruptcy and Suspension of Obligations for Payment of Debt (UUK-PKPU) in Indonesia. This law applies to situations where foreign parties are involved and the case extends beyond national and regional borders. The focus of this article is to examine the treatment of assets located abroad. Indonesia follows the territoriality principle, which means that the debtor's assets in foreign jurisdictions cannot be transferred to other countries unless bankruptcy decisions made by those countries are recognized. This study adopts a normative juridical research method to gather relevant materials such as concepts, theories, laws, and regulations pertaining to the subject matter. Due to the varying rules in each jurisdiction, it is challenging to determine the status of assets located in foreign countries. The key issue lies in whether domestic bankruptcy decisions are acknowledged and enforced in other jurisdictions, and vice versa. In conclusion, Indonesia should consider revising its cross-border bankruptcy laws and entering into international agreements or conventions to address these challenges effectively.